Selection of parent trees for Rubber (Hevea brasiliensis) breeding based on RAPD analysis - FETRINA OKTAVIA; MUDJI LASMININGSIH; KUSWANHADI KUSWANHADI (Nusantara Bioscience, 2011)
Abstract. Oktavia F, Lasminingsih M, Kuswanhadi. 2011. Selection of parent trees for Rubber (Hevea brasiliensis) breeding based on RAPD analysis. Nusantara Bioscience 3: 124-129. The parent trees’ clones usually originate from the previous generation having the potential of high production with better agronomical characters. Although, phenotype characters can determine the genetic variability among accessions, they are highly sensitive to environmental factors, so it is often difficult to identify the difference between closely related clones. The genetic variability or phylogenetic relationships among rubber clones can be analyzed using RAPD method, and based on the result, the parent trees can be selected. This research was aimed to analyze the genetic distance among rubber clones using RAPD method. Analysis was conducted on 45 rubber clones with 12 random primers. Pair-wise comparisons of unique and shared polymorphic amplification products were used to generate similarity coefficients. These coefficients were employed to construct a dendrogram by using an Unweighted Pair-Group Method with Arithmetical Averages (UPGMA). The amplification of genomic DNA from 45 clones yielded 2408 DNA fragments, ranging in size from 250 bp to 3000 bp. The range of genetic similarity matrix was very wide (59.18%-94.23%). It indicated that most of the clones have a low level of polymorphism. The lowest genetic similarity (59,18%) was found between RRIC 110 and AVROS 352 clones, while the highest (94.23%) was between IRR 41 and IRR 42 clones. Cluster analysis showed that 45 clones of rubber were divided into two groups, the biggest group consisted of 30 clones, while the other one consisted of 15 clones with a genetic similarity value of 0,73.